Notice to comply GCC sub-clause 54.1 and instructions in hacking and dismantle of R.C.C related items of bill of quantities - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the notice to comply GCC sub-clause 54.1 and instructions in hacking and dismantle of R.C.C related items of bill of quantities of BRAC University new campus project.